Life habits predispose osteoporosis in postmenopausal women in the neighborhood Libertador Simon Bolivar District of Sapallanga 2014 - Camposano Córdova, Yda Flor (2020)
OBJECTIVE: To identify the essential elements related to the main symptoms and signs of menopause, the risk factors in this stage as well as in the therapeutic approach that should be taken into account for appropriate management, comprehensive care, by professionals the health.METHOD: the inductive method was used descriptive approach, with a population made up of 35 women of Simon Bolivar neighborhood Sapallanga District. Data collection was through a survey - personal interview. According to the results it stated that regular consumption of coca leaves is therefore have no signs and symptoms that predispose the disease. RESULTS: The total study population is between the ages of 45 and 65, a number 35 representing 100%. Finding so 33 patients representing 94% have not undergone hysterectomy, a situation that has allowed the hormonal cycle of this population has continued, this feature will allow us to generalize the results to be a homogeneous sample. Most of the population of 32 patients representing 91% did not consume cigarettes, alcohol and other harmful habits; likewise they performed physical activities which means that if there is prevention of osteoporosis. Also 32 patients representing 91% consume the coca leaf chewed through. Meaning that this population has high calcium requirements and contributes to the prevention of osteoporosis.CONCLUSION: According to statistical results obtained in the research work in the study population (menopausal women) do not have osteoporosis, with the regular use of chewing coca leaves; as reviews of articles and magazines state that the coca leaf has a high percentage of calcium as properties that contribute to the predisposition of osteoporosis and no increases physical endurance.